Super platforms – going beyond bundling digital solutions - Addom, Benjamin K. (Technical Centre for Agricultural and Rural Cooperation, 2019)
Solutions that bundle multiple digital agricultural services have the capacity to unlock the potential of smallholder farmers. However, emerging ‘super platforms' are complex and their impacts need to be carefully assessed before being widely promoted in Africa.